Enhancing aerobic granule formation and stability in sequencing batch reactor using a staged organic loading rate strategy for wastewater treatment - Lee, Pui San; Suryati, Sulaiman; Noor Suraya, Romali; Nadiah, Mokhtar; Abdul Syukor, Abd Razak (IOP Publishing Ltd., 2025)
Aerobic granule sludge has emerged as a promising technology in wastewater treatment, achieving over 90% removal efficiency of pollutants, reducing land usage by as much as 75%, lowering costs by as much as 50%, and demonstrating superior resilience to shock loads and toxic compounds in comparison to conventional activated sludge systems. These advantages enhance operational efficiency and versatility across various wastewater types. However, it is known for its shortcomings, including long start-up times at low organic loading rates (OLR) and instability at high OLR. This study incorporated a staged OLR strategy to cultivate aerobic granules, addressing these limitations. Initially, the aerobic granules were cultivated at an OLR of 5 kg/m3/day for 28 days during Phase I, and then used to treat an OLR of 1 kg/m3/day during Phase II for another 42 days. The study demonstrated stable and effective performance, achieving more than 90% Chemical Oxygen Demand (COD) removal. Nitrogen (TN) and phosphorus (TP) removal efficiencies were about 60% and 80%, respectively. The system showed relatively consistent removal efficiencies after the transition to the lower OLR in Phase II. The mineral composition analysis revealed higher concentrations of calcium (Ca), magnesium (Mg), and iron (Fe) in Phase II compared to Phase I. Overall, the staged OLR strategy proved to be effective in cultivating stable aerobic granules with desirable properties. However, improvements are needed in the removal efficiencies of nitrogen and phosphorus. This approach offers a viable method for enhancing granule properties and stability in wastewater treatment applications.